Sleep-wake disorders in Alzheimer's disease: further genetic analyses in relation to objective sleep measures. (July 2020) - Yesavage, Jerome A.; Noda, Art; Heath, Alesha; McNerney, M. Windy; Domingue, Benjamin W.; Hernandez, Yozen; Benson, Gary; Hallmayer, Joachim; O'Hara, Ruth; Williams, Leanne M.; Goldstein-Piekarski, Andrea N.; Zeitzer, Jamie M.; et al.
ABSTRACT: This paper presents updated analyses on the genetic associations of sleep disruption in individuals with Alzheimer's disease (AD). We published previously a study of the association between single nucleotide polymorphisms (SNPs) found in eight genes related to circadian rhythms and objective measures of sleep-wake disturbances in 124 individuals with AD. Here, we present new relevant analyses using polygenic risk scores (PRS) and variable number tandem repeats (VNTRs) enumerations. PRS were calculated using the genetic data from the original participants and relevant genome wide association studies (GWAS). VNTRs for the same circadian rhythm genes studied with SNPs were obtained from a separate cohort of participants using whole genome sequencing (WGS). Objectively (wrist actigraphy) determined wake after sleep onset (WASO) was used as a measure of sleep disruption. None of the PRS were associated with sleep disturbance. Computer analyses using VNTRseek software generated a total of 30 VNTRs for the circadian-related genes but none appear relevant to our objective sleep measure. In addition, of 71 neurotransmitter function-related genes, 29 genes had VNTRs that differed from the reference VNTR, but it was not clear if any of these might affect circadian function in AD patients. Although we have not found in either the current analyses or in our previous published analyses of SNPs any direct linkages between identified genetic factors and WASO, research in this area remains in its infancy.